Acute necrotizing encephalopathy associated with lymphoma-associated hemophagocytic lymphohistiocytosis: A case report and literature review - Sun, Wenqiang; Fu, Changchang; Zhu, Xueping (Frontiers in Oncology, 2022)
Damage associated with lymphoma-associated hemophagocytic lymphohistiocytosis (LA-HLH) to the central nervous system (CNS) is not uncommon. However, the combination with brain damage resembling acute necrotizing encephalopathy (ANE) is rarely reported. Herein, we introduce the diagnosis and treatment of a case of ANE associated with LA-HLH in our hospital and review the relevant literature. After treatment, the child was discharged with only dysarthria and decreased sucking ability. The child is now discharged from the hospital for 6 months with regular follow-up. There were no disease recurrence signs. LA-HLH and ANE were related to cytokine storm. Therefore, early steroid application is essential for treating these diseases.